Finland in a Geopolitical Perspective - From Finlandization to Integration with NATO - Kaczmarek Krzysztof (2024)
The aim of this article is to analyse the determinants of changes in the foreign and security policy of the Republic of Finland and to answer the question of how this country's accession to NATO influenced the balance of power and the security environment in Northern Europe. The results of these analyses will allow us to understand how small states can shape the security environment at both the micro, meso, and macro scale.